DETERMINASI PROFITABILITAS ASURANSI JIWA SYARIAH DI INDONESIA - Farhan Rafii Putra Suharto, Farhan (2021)
This study aims to analyze the effect of premium income, solvency, and asset growth on the profitability of Islamic life insurance in Indonesia. This study uses a quantitative approach. For the sample used by this researcher, there are 19 sharia life insurance companies that are officially registered with the Financial Services Authority. The data sample selection was obtained using purposive sampling technique. The analytical technique used to determine the magnitude of the effect is using panel data regression analysis, f-test, t-test and coefficient of determination test with Eviews version 8.0 program. This study uses secondary data with a period starting from 2017 to 2019, which comes from the official website of each company under study. The results of the tests carried out show that the variables of premium income, solvency and asset growth have a significant effect on profitability simultaneously. While the partial test found that premium income did not have a significant positive effect on profitability, solvency had a significant positive effect on profitability, and asset growth had no significant negative effect.